Uso de álcool e tabaco entre universitários de nutrição de uma universidade pública - Andrade, Laerson da Silva de (2019)
The use of psychoactive substances among university students has a higher prevalence when compared to the general population. Thus, the objective of the present study was to characterize the profile of alcohol and tobacco use, as well as the associated factors, among university students of the Nutrition course of a public university. For analysis of the data, univariate analysis was used, and the estimates provided by the bivariate analysis (Chi-square and Fisher) were expressed as Prevalence Ratio and Confidence Interval. Finally, for the multivariate analysis, the Binary Logistic Regression was performed. Variables associated with the outcome at a level of significance less than or equal to 25% were included in the multivariate analysis. The study covered 159 students enrolled in the Nutrition course, which corresponds to 69.43% of students enrolled in 2018. There was a predominance of females (87.9%), in the age group of 18-24 years old (88%), (41.8%) and evangelical (36.7%), economy class B (62%). The highest ethnic groups were Caucasoide / White (50%) and Brown / Mulato (39.9%). The prevalence of alcohol use in the last 12 months, Binge Dink in the last 12 months in the last 30 days were: 34.6%, 46.4% and 35.9%, respectively. Of these, 73.5% are low risk users and 26.6% moderate risk. Regarding smoking, 28.7% reported having consumed tobacco at some point in their lives, and in the last 12 months consumption prevalence was 9.1% in the last 3 months, 6.5% and in Last 30 days, of 5.4%. In the sample, 5.1% have a very low dependence. In the multivariate analysis, the significant predictors for alcohol use and abuse were sex, age of experimentation, religious practice and paid activity. Already for tobacco use were Sex, Religious practice and age of tobacco experimentation. Studies on the use of SPA’s among university students are necessary to understand the most diverse dimensions of drug use in society.